KESIAPAN PENGELOLAAN OBJEK WISATA UNGGULAN PROGRAM WISATA HALAL (HALAL TOURISM) KOTA BANDA ACEH - Cut Nuryasmin; M. Hafizul Furqan (Jurnal Samudra Geografi, 2023)
The purpose of this study was to determine government support for the readiness of managing halal tourism objects (halal tourism) and to determine the readiness of destinations for the management of halal tourism objects (halal tourism) in the City of Banda Aceh. The method used is a qualitative method. The research location was carried out at the Baiturrahman Great Mosque, the Syiah Kuala tomb, the boat above the house, the tsunami museum and the PLTD Apung. Data collection techniques used interview techniques, the informants in this study were the Banda Aceh City tourism office and the manager of the leading tourist objects of Banda Aceh City. The analysis technique uses basic triangulation. The results of the research seen from the aspect of government support show that the management of leading tourist objects is still not ready to implement the halal tourism program in Banda Aceh City. Meanwhile, when viewed from the aspect of the destination, it shows that the management of leading tourist objects is ready to implement a halal tourism program in Banda Aceh City